Effects of Online Learning Readiness and Online Self-Regulated English Learning on Satisfaction with Online English Learning Experience During the COVID-19 Pandemic - Sarah W. S. Ip; Wai-Ming To (Behavioral Sciences)
The COVID-19 pandemic has caused major changes in pedagogical practices worldwide. As COVID-19 cases increased, universities had to move their teaching online, requiring both instructors and students to engage through online learning platforms. This study explored the effects of students’ online learning readiness and online self-regulated English learning on their satisfaction with the online English learning experience. Additionally, it investigated whether and how online learning readiness and online self-regulated English learning influenced students’ perceived English self-efficacy which could in turn influence their satisfaction with the online English learning experience. Data were collected from 163 university students in Macau, China. The results of partial least squares structural equation modeling showed that students’ online learning readiness significantly influenced their satisfaction with the online English learning experience directly and indirectly through online self-regulated English learning. Furthermore, online learning readiness affected students’ perceived English self-efficacy. However, online self-regulated English learning did not significantly impact students’ perceived English self-efficacy, and there was no significant link between students’ perceived English self-efficacy and their satisfaction with the online English learning experience. The implications of this study are given.